Integrasi Teknologi di Gudang Farmasi: Tantangan dan Peluang untuk Meningkatkan Kualitas dan Keamanan Obat - Jajang Japar Sodik; Asep Kamal Sahroni (An-Najat, 2024)
Pharmaceutical warehouses play a crucial role in maintaining the quality and integrity of medicines within the pharmaceutical supply chain. Proper storage and effective management of these facilities are key to ensuring the effectiveness, safety, and availability of medicines. However, managing pharmaceutical warehouses poses several challenges, such as inventory control, maintaining optimal storage conditions, and detecting genotoxic contaminants, which can impact the quality and availability of medicines. Literature search was conducted across several databases, including PubMed, ScienceDirect, and Google Scholar, using keywords such as "Pharmaceutical Warehouse Management", "Pharmaceutical Warehouses", and "Pharmaceutical Warehouse Operations". The literature review findings suggest that technology integration, such as the adoption of blockchain technology, barcode scanning, and RFID technology, holds the potential to enhance operational efficiency and medicine quality in pharmaceutical warehouses. Nevertheless, challenges such as system integration, data security, and the need for staff training also need to be addressed in adopting these technologies. Future research should explore strategies to overcome these challenges and the impact of technology adoption on the overall efficiency and effectiveness of pharmaceutical supply chain management